The Influence of Leadership, Work Discipline, and Work Motivation on the Performance of Financial Administration Personnel at Satker Pusku Mabes TNI - Sunarti, Endang (Dinasti Publisher, 2025)
Personnel performance is critical determinant of organizational success, particularly in structured environments such as military institutions. At Satker Pusku Mabes TNI, financial administration plays a vital role in ensuring operational continuity, yet challenges in achieving optimal performance remain. This study investigates the influence of leadership, work discipline, and work motivation on the performance of financial administration personnel. The research employs a quantitative approach, with data collected through surveys of 60 respondents drawn from a total population of 126 personnel. Statistical analyses, including multiple linear regression, were conducted using SPSS version 25. The findings reveal that leadership, work discipline, and work motivation significantly and positively influence personnel performance both individually and collectively. Leadership demonstrates the ability to guide and inspire personnel, while work discipline ensures adherence to organizational rules and enhances accountability. Work motivation fosters employee engagement and productivity through intrinsic and extrinsic factors. The coefficient of determination (R²) indicates that 81.3% of performance variations are explained by these three variables, with the remaining 18.7% attributed to other factors. This study underscores the importance of integrating effective leadership, discipline, and motivation strategies to enhance performance in high-stakes environments. Future research should explore additional variables such as organizational culture and peer support.